Customer relationship management practices affecting customer loyalty supporting small airline carriers in Ghana. (2018) - Quaye, Daniel M.; Mensah, Isaac; Amoah-Mensah, Aborampah
The airline industry in Ghana has experienced some significant growth largely driven by the influx of local and foreign airline operators. In this paper, six CRM practices namely: complaint handling, trust, commitment, communication, competences and social bonds were identified and proposed as drivers of customer loyalty through satisfaction. 341 passengers of small airline carriers in Ghana were sampled for this research. SEM was used to analyse the filed data. While the paper found a partial mediation, trust and compliant handling are the two significant drivers of customer loyalty of which the latter is the strongest predictor of customer loyalty. The paper recommends that managers of small airlines carriers should be honest, provide reliable and quality services to boost trust and confidence of passengers. They must create strong social relation with passengers as a strategy to build trust and instil confidence in them. This paper has presented industry specific evidence for small airline carriers which is non-existent in academic literature.